2019
DOI: 10.1177/1550147719847127
|View full text |Cite
|
Sign up to set email alerts
|

Internet of things in healthcare monitoring to enhance acquisition performance of respiratory disorder sensors

Abstract: The implementation of the Internet of things in healthcare is a promising challenge to achieve coverage for a bigger number of users in different places at lower costs. Internet of things might mean better technology regarding response time and proper control of medical parameters. This study introduces an Internet-of-things system for healthcare with possibilities to control medical variables according to recent breakthroughs in sensors and data processing. The goal of the system is to optimize the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Ramírez López et al 4 investigate an Internet-of-things system for healthcare to control medical variables according to recent breakthroughs in sensors and data processing. One of the contributions of this work is the reduction in energy consumption with the optimization of data acquisition integrated into a secure architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Ramírez López et al 4 investigate an Internet-of-things system for healthcare to control medical variables according to recent breakthroughs in sensors and data processing. One of the contributions of this work is the reduction in energy consumption with the optimization of data acquisition integrated into a secure architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Yi et al 44 proposed an MQTT-based mobile health monitoring system, where the server is constructed using Model, View, and Controller (MVC) architecture and subscribe and publish the communication using an Android platform. Salunke and Nerkar, 45 Song et al, 46 Kadhim et al, 47 and Ramírez et al 48 proposed various techniques for healthcare monitoring remotely through MQTT protocols. The performance of different asymmetric key cryptographic algorithms includes RSA, ECC are analyzed, observed that ECC is using small keys and providing better security, whereas RSA is taking lesser execution time in the process of data encryption.…”
Section: Related Workmentioning
confidence: 99%
“…The big data produced by the Internet of Things possesses various qualities if we compare it with the general big data since the various kinds of gathered, of which most of the classical qualities including variety, heterogeneity, noise, high redundancy and unstructured feature. Even though the recent data of the Internet of Things does not dominate big data, by the year 2030, the sensor amount will have reached a trillion, and the data of the Internet of Things will have been the most significant part in big data, in view of the HP forecast [2]. Intel reported that big data in The Internet of Things possesses three characteristics conforming to the paradigm of big data: (i) abundant terminals which produce masses of data.…”
Section: Relationship Between Iot and Big Datamentioning
confidence: 99%